Avaliação da política de segurança alimentar implementada através dos restaurantes populares do Rio Grande do Norte - Silva, Gidyenne Christiane Bandeira (2008)
This survey has to general objective to evaluate the Food Safety Policy implemented by Restaurantes Populares do Rio Grande do Norte. The survey is qualitative of type exploratory and descriptive. The universe of survey is all Units of Food and Nutrition (UAN) of the Restaurantes Populares do Rio Grande do Norte. To collects of data were used two instruments: interview and form. The interviews were intended to analyze the four axes of the Food Safety: access, food quality, production and marketing of food and organizational arrangement. The form was used to check the quality of nutrition and sanitary-hygienic food served. We used two types of forms: a spreadsheet with the weekly menu and the portions served to verify that the meals serve the nutritional needs proposed by the program; and the check-list of ANVISA to verify the sanitary-hygienic conditions in each unit. Through the survey data and analyses made observe that the access category have some problems such as lack of registration, lack of advertising of Restaurants and wastage of public resources, making policy that should be of included in a policy of exclusion. In the nutritional aspect there is neglect on the daily nutritional goal, because it is not accomplished nutritional analysis of menu offered, the nutritionists do not know what should be the nutritional value of meals served; in the hygienic-health aspect trough the problems identified is concludes that there is no guarantee of food quality hygienic-sanitary, committing the program as a Food Safety Program. About the production and marketing of food is observed some problems as: the goal of sale of meals is not achieved in full, the purchase of genres does not stimulate the local economy, nor generates jobs and income, and inefficient performance of the MEIOS's supervision. In the analysis of organizational arrangement is concluded that the partnerships are beneficial, despite some negative points, therefore, are these partnerships the problems of non-compliance, as both the MEIOS and Nutriti of important criteria established in the partnership. Therefore, it is understood that the Programa Restaurantes Populares in its original formulation is proposed to be a food safety policy, but has some problems that impossible to meet its goal, making it unprofitable like Food Safety Policy